(untitled) (Fiep Bulletin - online, 2014)
The media makes possible us instantaneous and simultaneous interactions, mainly in the transmissions of several games, in several places, at the same time. This work, therefore, he/she has as objective, to analyze the symbolic construction of the soccer and of the player done by a newspaper of the state of São Paulo, regarding World cup of 2002, accomplished in South Korea and Japan. For this, it was used as material, the supplement of sport of the newspaper Leaf of São Paulo, in a period previous to the World cup, during and after the same. Some aspects observed in the newspapers tell respect the idolatrização certain players, even if previously the cup, they went white of several critics and doubts, as the case of Rivaldo. The collectivity representation also offers a significant characteristic when observing headlines that initially treat the technician as authoritarian and stubborn for later to place him/it as a conciliatory one, "big fater", boss of the "family Scolari." In the same way, it was noticed that what could affect or to oppose this collectivity were excluded sumariamente of the newspapers, in other words, Romário. The symbolic construction of three "R’s", in compensation to a real existence of four "R’s" in the selection demonstrates him/it as the media influences and it builds visions, values and representations. This way, we can end, in this phase of our analysis, that the headlines and news of the newspaper the Leaf of São Paulo brings for the readers an optimistic and fragmented vision of the selection, where in spite of every minute if it contemplates the union of the such "family positively Scolari", for several times if he/she pointed out the difficulties and limitations certain individual sections or players. This looks ambiguity is structural factor of the relationships social, cultural and sporting of the Brazilian society.